PENGEMBANGAN PEMBELAJARAN PEMERANAN TEATER DAERAH MELALUI KETOPRAK PADA PROGRAM KEAHLIAN SENI TEATER SMKN 1 KASIHAN BANTUL - Eko Santoso (Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
Theater Expertise Program of SMKN 1 Kasihan Bantul offers modern theater and local theater in its learning program. “Ketoprak” is the major subject taught in the local theater. Hence, the learning of acting also conforms to the acting of “ketoprak”. The objective of learning development in grade X to grade XII is to provide students with the abilities needed to play roles in various forms of “ketoprak”. The current research aims to expose the underlying consideration of determining “ketoprak” as the major subject of local theater learning in Theater Expertise Program at SMKN 1 Kasihan Bantul, and how the school attempts to develop the learning process of this subject. Qualitative research was employed in August to October 2021. Data collected through documentation study, interviews, and observation. The sources of data were field notes, documentation of students’ work, and interview results. Results of the study demonstrate that the popularity and the existence of “ketoprak” turn out to be the essential justification of determining “ketoprak” as the major subject of the local theater acting learning; besides, it is a form of local theater preservation and cultural development in theater as well. Mixing modern theater acting techniques with “ketoprak” acting style is done to improve local theater acting learning. The combined technique is subsequently employed in the production of “ketoprak lesung”, “ketoprak ongkek”, and “ketoprak pendapan” performances. The most recent attempt in this line of work is creating cinematographic (film) “ketoprak” although the techniques of acting in front of the camera have not yet been fully implemented